2022
DOI: 10.14311/app.2022.33.0245
|View full text |Cite
|
Sign up to set email alerts
|

Durability of high belite cement as new technical solution for concrete

Abstract: The study presents an investigation on the durability performance of concretes produced with an industrial scale high belite cement. This binder, thanks to the high amount of C-S-H gel and the lower C3S/C2S ratio, is characterized by high durability properties. Good resistance to freeze/thaw cycles, very low chloride migration and excellent resistance to sulfate attack were demonstrated. Theaccelerated carbonation test revealed that the belite cement, due to the high C2S phase amount, is able to increase its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…During the durability tests, there was no distortion of the samples and the compressive strengths did not differ from the strengths of the samples stored in the humidity chamber. As many authors [17,18] confirmed, belite based binders show high durability and good resistance against freeze/thaw cycles which might be one of the main advantages of using alternative belite binders instead of conventional cement.…”
Section: Phase S-g 0 S-g LI S-g Cu S-g K S-g Napmentioning
confidence: 96%
“…During the durability tests, there was no distortion of the samples and the compressive strengths did not differ from the strengths of the samples stored in the humidity chamber. As many authors [17,18] confirmed, belite based binders show high durability and good resistance against freeze/thaw cycles which might be one of the main advantages of using alternative belite binders instead of conventional cement.…”
Section: Phase S-g 0 S-g LI S-g Cu S-g K S-g Napmentioning
confidence: 96%